Politeness in Minang Language in Tenggelamnya Kapal Van Der Wijck Film - Siti Isnaniah; Syihaabul Huda (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The principle of politness in using language should be concerned by language users in communication. Film industry in Indonesia can be example for the people who watch and listen to the language used. This, ofcourse, will affect the use of language use in Indonesian society. The objective of the article is to study about language politeness in Minang language used by the characters of Hayati and Zainudin in communicating. The communication practice among characters was studied to identify the politeness of language used. The research was descriptive qualitative using content analysis and literary study. The source of the data was a film entitled "Tenggelamnya Kapal van der Wijck" from novel by Hamka. The data in this research came from the characters' dialogue in this film. The data, then, were analyzed using the theory of language politeness to identify the difference of language politeness between characters of Hayati and Zainudin. The result of the research shows that Minang language used by the characters applied the rule of language politeness.Keywords: Language politeness; language meaning; language harmony.